Restless leg syndrome in children with celiac disease - Işıkay, Şedat; Işıkay, Nurgül; Per, Hüseyin; Çarman, Kürşat Bora; Kocamaz, Halil (Turkish Journal of Pediatrics, 2018)
Celiac disease (CD) is an immune-mediated enteropathy triggered by ingestion of dietary gluten in genetically predisposed individuals. The aim of the study was to determine the prevalence of restless leg syndrome (RLS) in children with CD and to investigate the associated factors for RLS. Totally 494 children with the ages ranging between 11-18 years were included. Among those, 226 were under follow-up with CD and constituted the study group while other 268 children did not have any symptoms or signs associated with CD and established the control group. The demographic data, educational status and routine laboratory data of children including complete blood count, ferritin, vitamin B12, foliate and 25 (OH) vitamin D levels were recorded. The RLS prevalence and associated symptoms of children were defined with a questionnaire. There was no statistically significant difference between the 2 groups regarding the age and gender. Moreover, RLS prevalence was also similar in both groups (3.5% vs 3.0% in CD and control groups, respectively, p=0.98). However, interestingly, in CD group, the mean age of the patients at the onset of RLS symptoms was statistically significantly younger (p=0.02) and the disease was more severe (p=0.026) than the control group. In correlation analysis in CD group, the RLS severity significantly negatively correlated with serum ferritin, folic acid or 25 (OH) vitamin D levels in Celiac disease group. In this study we did not determine an increased prevalence of RLS in children with CD. However, in CD group, the age at the onset of RLS symptoms was significantly younger and the disease was more severe in CD group compared with the control cases.
Keywords: Anemia; Celiac disease; Children; Restless leg syndrome